2023
DOI: 10.18280/jesa.560112
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal GA-Based Backstepping Control Scheme for a MIMO Nonlinear System

Abstract: In the presence of external disturbances, a backstepping control scheme based a genetic algorithm (GA) is built with the objective of tracking a desired trajectory of robot manipulators. The nonlinear-coupled higher order dynamic model of an n-link robot manipulator is first briefly presented. Then, a traditional backstepping control system (BSC) creates a two-link robotic manipulator position tracking control. Furthermore, a mix of nonlinear control and artificial intelligence is suggested for manipulator rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Such challenges, including the introduction of undesirable variables like modeling uncertainty, the influence of measurement noise, and effects stemming from overlooked nonlinear dynamics, have necessitated the development of highly effective synthesis techniques. It has been observed that these techniques necessitate the synthesis of controllers which strike a balance between robust loop system stability and optimal performance [1]. Importantly, this balance is not merely restricted to the nominal operating speed of the system under control but also extends to numerous conditions wherein the synthetic model's parameters can exhibit significant variability.…”
Section: Introductionmentioning
confidence: 99%
“…Such challenges, including the introduction of undesirable variables like modeling uncertainty, the influence of measurement noise, and effects stemming from overlooked nonlinear dynamics, have necessitated the development of highly effective synthesis techniques. It has been observed that these techniques necessitate the synthesis of controllers which strike a balance between robust loop system stability and optimal performance [1]. Importantly, this balance is not merely restricted to the nominal operating speed of the system under control but also extends to numerous conditions wherein the synthetic model's parameters can exhibit significant variability.…”
Section: Introductionmentioning
confidence: 99%